Los derechos en el constitucionalismo: tipología y tutela «multilevel» - Alvarez Conde, Enrique; Tur Ausina, Rosario (Teoría y Realidad Constitucional, 2007)
The survey pretends an approach to the characteristic multilevel protection of rights throughly studied in the last times. Starting from previous considerations that should highlight the value of fundamental rights in constitutionalism, we reach today a globalized world in which the benefits that citizens receive, as well as the juridical status, are exceeded by different levels of acknowledgement and protection in search of a perfect fitting. Therefore, the survey tackles such a problem tacking into account, on the one hand, the complexity the new challewnges represent for the classical rights (biotechnology, collective rights, environment, etc.) and at the same time, on the other hand, noticing that the protection is «distributed» amongst many different and varied levels. If States and international organisms were until now the «natural» guarantors of rights, we must take into consideration, from this very moment, that the contribution of protection in the under state levels (regional autonomous, local), but as well the emphasis that appears in the private field. Definitely, the multileval protection of rights is one of the great challenges of the contemporary democracies.